2015
DOI: 10.1177/1087057114548833
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Compound Screening against RNA Editing Identifies Trypanocidal Agents

Abstract: Most mitochondrial messenger RNAs in trypanosomatid pathogens undergo a unique type of posttranscriptional modification involving insertion and/or deletion of uridylates. This process, RNA editing, is catalyzed by a multiprotein complex (~1.6 MDa), the editosome. Knockdown of core editosome proteins compromises mitochondrial function and, ultimately, parasite viability. Hence, because the editosome is restricted to trypanosomatids, it serves as a unique drug target in these pathogens. Currently, there is a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The different diseases represent severe problems mostly in tropical and subtropical regions of the globe and are responsible for about one million deaths per year [1]. A promising drug target for the different diseases is the unique mRNA editing process that takes place within the mitochondria of kinetoplastids [2,3]. Mitochondrial pre-mRNAs in these organisms undergo a multistep RNA editing reaction, which leads to the maturation of mRNAs and by introducing variation, it may contribute to the generation of protein diversity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The different diseases represent severe problems mostly in tropical and subtropical regions of the globe and are responsible for about one million deaths per year [1]. A promising drug target for the different diseases is the unique mRNA editing process that takes place within the mitochondria of kinetoplastids [2,3]. Mitochondrial pre-mRNAs in these organisms undergo a multistep RNA editing reaction, which leads to the maturation of mRNAs and by introducing variation, it may contribute to the generation of protein diversity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Most likely it acts on several T. brucei pathways and the exact mode of action is still not entirely clear ( 42 , 44 , 45 ). Suramin and its analogue NF 023 have previously been identified as inhibitor of RNA editing in vitro ( 32 , 46 ). One study suggested that NF 023 and suramin ‘are either acting at a step following the endonuclease cleavage or alternatively having global effects on the editing complex’ ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many chemotherapy drugs that require infusion, such as the bright blue compound mitroxantrone, an agent which has a variety of activities in cells, have limited solubility and may induce nonspecific aggregation of the protein or assay reagents in high throughput screening . A good deal of time can be lost to these nonspecific aggregators, which can have misleading activity in a variety of different assays at low micromolar concentrations . Mitroxantrone even turned up in a preliminary screen to identify inhibitors of uridylyation of the peptide linked to the genome, VPg, to VPgpU by the coxsackie virus A24 polymerase in the author's group.…”
Section: Repurposing As a Path To New Drugsmentioning
confidence: 99%
“…Thus, the approximately 4000 compounds used in the clinic are now being reinvestigated, to see what other treatments they could provide for difficult to treat conditions. Searching approved drugs for new purposes has been aided by commercially available compilations of drugs approved by the FDA, such as the Prestwick Chemical Library, the Library of Pharmacologically Active Compounds (LOPAC1280) and others, or specific libraries assembled for various purposes, such as those targeting RNA‐protein interactions or kinases. The “Drug Repurposing Hub” (http://www.broadinstitute.org/repurposing), consisting of both a reliable physical source for approved drugs, as well as a virtual library describing their characteristics, will certainly help to identify new uses for the existing pantheon .…”
Section: Introductionmentioning
confidence: 99%